The Effect of the Parameters on Al 7075 Coated with MAO Method by Adding Nano Ti-Powder - Özcan, Mehmet Erbil; Ozler, Latıf (My University, 2022)
Coating processes are carried out in many areas of industry to improve the surface properties of materials such as wear and corrosion resistance or appearance. One of these coating processes is ceramic-based surface coatings. In order to obtain harder, denser and more uniform coatings, the substrate material is coated with a ceramic-based material at the desired thickness. In this study, 7075 series aluminum was coated with nano Ti powder and non-additive micro arc oxidation (MAO) method in a solution consisting of KOH, NaAlO2 and Na3PO4, and the effects of process parameters on coating thickness and wear behavior were experimentally investigated and the results were analyzed. According to the results obtained, it was observed that as the coating voltage, frequency and coating time increased, the wear rate decreased and a harder structure against wear is obtained. In addition, it was determined that the samples with nano titanium powder were less worn than the non-additive samples. According to SEM, EDX and XRD analyses, Al2O3 phase was observed in the coatings made without adding titanium particles; It has been observed that in addition to the Al2O3 main phase, TiO2 and SiO phases are also formed in titanium doped coatings.
Keywords: Coating; Wear; Titanium; AA7075; Micro Arc Oxidation